The physiotherapy management of thoracotomy patients: a survey of current practice in Gauteng - Schwellnus, Liezel Brunhilde (My University, 2015)
Physiotherapy treatment is an essential component in the management of patients after open thoracic surgery in order to prevent respiratory complications and improve shoulder and thoracic cage mobility (Reeve, 2008). To date, limited research has been done on patients who have had open thoracotomy surgery. The body of knowledge and evidence on physiotherapy management of thoracotomy patients need to be addressed. The aim of this research report was to establish which physiotherapy treatment modalities are used in the management of thoracotomy patients in Gauteng. Methods: A self-administered questionnaire was used to obtain the data for this descriptive, cross sectional study. A sample of convenience was used and questionnaires were distributed to all physiotherapists registered with the SASP (South African Society of Physiotherapy) in Gauteng. Ethical clearance was obtained from the University of the Witwatersrand Human Research Ethics committee. An expert panel established the content validity of the questionnaire. The provisional questionnaire was piloted electronically via survey monkey. Invitations for participation in the main study were sent out after amendments were made to the questionnaire following the pilot study. Data for the main study was collected over a period of two months. Results: The questionnaire was distributed to 1389 physiotherapists registered with the SASP in Gauteng. Three hundred and twenty three physiotherapists (23.3%) responded. Only 141 of the responders were eligible for inclusion in the study. Ninety-five respondents indicated that they only see thoracotomy patients while still in hospital, 25 said they see these patients only after discharge while 21 respondents treated these patients both during and after hospital stay. The majority of physiotherapists who treat thoracotomy patients were females between the ages of 23 to 69. Results indicated that pre-operative physiotherapy management was most commonly determined by the patients’ risk profiles and consisted of information and respiratory techniques. Prophylactic post-operative management was high and in accordance with studies from Reeve et al (2007) and Agostini et al (2013). The modalities used most commonly were respiratory techniques with deep breathing exercise (97.6%: n=83), coughing (95.3%; n=81) and ACBT (82.4%: n=70), scoring highest. Exercise interventions used were early mobilistation (95.3%; n=81), trunk- (85.9; n=73) and upper limb mobility exercises (91.8%; n=78). Limited modalities focused on treating pain with OMT (11.8%; n=10) and transcutaneous electrical nerve stimulation (12.9%; n=11), being the modalities of choice. Post-hospital discharge physiotherapy management was uncommon with only 32.6% (n=46) of respondents treating patients during this phase. During the first six weeks after discharge the main focus of treatment was on respiratory difficulties (64%; n=41). After six weeks the focus moved to treating pain (57.8%; n=37). Management choices during all phases of contact with patients undergoing open thoracotomies were influenced by personal experience and established practice protocols as mentioned in the questionnaire. Conclusion: High quality evidence regarding the management of patients after open thoracic surgery still seems to be limited when compared to other high risk surgery groups (Reeve, 2008). Considering this, it seems that physiotherapists in Gauteng are using the relevant techniques to prevent and manage postoperative pulmonary complications (PPCs) in patients that undergo open thoracic surgery. Pre- and post-operative techniques most commonly used were respiratory techniques and early mobilisation. Management choices seem to be predominantly affected by experience and established practice protocol. There is a lack in pain management for these patients both during and after hospital stay.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Physiotherapy Johannesburg, 2015